2018
DOI: 10.13171/mjc72/01808051520-ouass
|View full text |Cite
|
Sign up to set email alerts
|

Removal of trivalent chromium ions from aqueous solutions by Sodium polyacrylate beads

Abstract: In the present study, the performance of sodium polyacrylate beads on the removal of trivalent chromium Cr (III) from aqueous solutions was evaluated using several techniques such as Fourier Transformed Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Analysis (EDAX), Inductively Coupled Plasma (ICP) and Atomic Adsorption Spectroscopy (AAS). On one hand, the characterization of dry PANa beads was carried out through FTIR and the surface morphology was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The band arising due to vibrational ν(C=N) mode at 1643 cm -1 (m) in the free 1,10phenanthroline monohydrate was shifted to lower frequencies, at 1573.79 cm -1 (m) in [Fe(imida.)2(phen.)(H2O)2]SO4. This shift suggested that 1,10-phenanthroline binds with the metal center via ring nitrogen appeared at 646.37cm -1 due to ν (Fe…N) [32,33]. The 1 HNMR spectra (Figure 2) were recorded for the mixed ligands and its metal complex in DMSO as the solvent and showed the following chemical shifts: multiple and signal chemical shifts between 7.13-8.8 ppm belong to the protons in aromatic rings, the singlet chemical shift at 8.39,7.89 ppm is attributed to the proton attached to C=N group.…”
Section: Resultsmentioning
confidence: 96%
“…The band arising due to vibrational ν(C=N) mode at 1643 cm -1 (m) in the free 1,10phenanthroline monohydrate was shifted to lower frequencies, at 1573.79 cm -1 (m) in [Fe(imida.)2(phen.)(H2O)2]SO4. This shift suggested that 1,10-phenanthroline binds with the metal center via ring nitrogen appeared at 646.37cm -1 due to ν (Fe…N) [32,33]. The 1 HNMR spectra (Figure 2) were recorded for the mixed ligands and its metal complex in DMSO as the solvent and showed the following chemical shifts: multiple and signal chemical shifts between 7.13-8.8 ppm belong to the protons in aromatic rings, the singlet chemical shift at 8.39,7.89 ppm is attributed to the proton attached to C=N group.…”
Section: Resultsmentioning
confidence: 96%
“…The Langmuir model and Freundlich model. The Langmuir eq (5) and Freundlich eq (6) equations are presented in Table 2 25 . Table 2.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Adsorption technique is one of the most effective processes of advanced wastewater treatment. It is superior to other techniques in terms of flexibility and simplicity of design, initial cost, insensitivity to toxic pollutants and ease of operation [3][4][5][6] . Many adsorbents are widely used such as activated carbon 7 , chitosan [8][9][10][11][12] , clay [13][14][15][16] and calcium carbonate [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Superabsorbent polymer hydrogels are widely used in daily life, for example, in medical and personal hygiene products for absorption of water and biological fluids . Other applications concern their use as smart separation media in wastewater treatment and removal of organic and inorganic pollutants such as dyes and heavy ions, for desalination of saline water to satisfy human consumption and other needs, or inversion of the desalination process to convert osmotic pressure into mechanical energy in an alternating swelling–shrinking manner, amongst other applications . Polyacrylic acid (PAA) hydrogels are usually synthesized in an aqueous solution polymerization or inverse suspension polymerization and subsequently treated for partial or full neutralization with, for example, sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%